Poverty Eradication Efforts in Iraq and Its Challenges in the Perspective of the Sustainable Development Goals (SDGs) - Ammal Yasser (Open Access Indonesia Journal of Social Sciences, 2023)
Iraq faces high levels of poverty, exacerbated by conflict and political crisis. The sustainable development goals (SDGs) offer a framework for overcoming poverty. This research aims to explore efforts to eradicate poverty in Iraq and its challenges from an SDGs perspective. This qualitative study uses in-depth interviews with 15 key informants from the government, non-governmental organizations, and academics in Iraq. Data were analyzed using thematic analysis. This research found that Iraq has made several efforts to alleviate poverty, including social assistance programs, investment in education and health, and economic reform. However, these efforts face various challenges, such as corruption, weak infrastructure, and political instability. In conclusion, Iraq still has a long way to go to achieve the SDGs regarding poverty alleviation. More targeted and sustainable efforts are needed to overcome existing challenges.